PD-L1 and epithelial-mesenchymal transition in circulating tumor cells from non-small cell lung cancer patients: A molecular shield to evade immune system?. (2nd December 2017) - Raimondi, Cristina; Carpino, Guido; Nicolazzo, Chiara; Gradilone, Angela; Gianni, Walter; Gelibter, Alain; Gaudio, Eugenio; Cortesi, Enrico; Gazzaniga, Paola
ABSTRACT: The programmed cell death 1 (PD-1)/PD-1 ligand 1 (PD-L1) pathway has emerged as a critical inhibitory pathway regulating T-cell response in non-small-cell lung cancer (NSCLC), and the development of PD-1/PD-L1 inhibitors has changed the landscape of NSCLC therapy. Nevertheless, the high degree of non-responders demonstrates that we are still far from completely understanding the events underlying tumor immune resistance. Although the expression of PD-L1 in tumor tissue has been correlated with clinical response to anti PD-1 inhibitors, the ability of this marker to discriminate the subgroup of patients who derive benefit from immunotherapy is suboptimal. Circulating tumor cells (CTCs), as an accessible source of tumor for biologic characterization that can be serially obtained with minimally invasive procedure, hold significant promise to facilitate treatment-specific biomarkers discovery. We recently demonstrated that the presence of PD-L1 on CTCs apparently predicts resistance to the anti-PD-1 Nivolumab in metastatic NSCLC patients and that PD-L1 positive CTCs usually have an elongated morphology that can be ascribed to epithelial–mesenchymal transition (EMT). We here demonstrate for the first time that PD-L1 positive CTCs isolated from NSCLC patients are characterized by partial EMT phenotype, and hypothesize that the co-expression of PD-L1 and EMT markers might represent for these cells a possible molecular background for immune escape.